Enhancing students' historical empathy and achievement in social studies using visual images - Aguilar, Marck Ferdinand A.; Oyzon, Maria Vanessa P. Lusung; Twayana, Czarina Agcaoili; Calingasan, Lorina Y. (Quezon City College of Education, University of the Philippines Diliman, 2019)
Few studies have investigated student's historical thinking skills in the Philippines. From these studies, there is a dearth of investigating how students can develop empathetic thinking and perspective-taking in learning history. This study focused on the enhancement of student's historical empathy and achievement in Social Studies using visual images. It sought to answer the following questions: (1) is there a significant difference between the Historical Empathy of students exposed to Lecture-Based Teaching and students exposed to Visual Images; (2) is there a significant difference between the academic achievement of students exposed to Lecture-Based Teaching and students exposed to Visual Images; (3) is there a relationship between Historical Empathy and the academic achievement of students exposed to Visual Images; and (4) how did students practice historical empathy inside the classroom. This study used a mixed-method design that gave an equal priority to qualitative and quantitative data. The participants of the study were 88 grade eight junior high school students from a private-sectarian school in Antipolo City during the academic year 2017-2018. This study employed four research instruments to gather data: academic achievement in social studies, researcher-made historical empathy scale, classroom observation, and classroom instructional plan. Significant differences in academic achievement and historical empathy scale results were determined and analyzed through t-test dependent and independent. The Pearson-r and Spearman-Rho were used to determine the relationship between Academic Achievement and Historical Empathy Scale scores of students exposed to Visual Images. The researcher found that there is a significant difference in the Historical Empathy scores of students exposed to lecture-based teaching and students exposed to Visual Images. Students who used visual images significantly increased their academic achievement scores than students exposed in lecture-based teaching. The study reveals a weak correlation in the students' historical empathy scores to their academic achievement. Moreover, students who were exposed to Visual Images display Historical Empathy through classroom discussions and activities. In light with the findings of the study, the researcher concluded that using Visual Images improves students' Historical Empathy and enhances academic achievement in Social Studies. Also, it was found out that that Visual Images are effective resources for History Teaching and allow students to manifest Historical Empathy.
Thesis
Includes bibliographical references (pages 96-110)
Keywords: Social studies -- Study and teaching (Secondary) -- Philippines -- Antipolo City; Academic achievement -- Philippines -- Antipolo City; Visual perception -- Philippines -- Antipolo City; Teaching -- Aids and devices. -- Philippines -- Antipolo City